ANALISIS PENGUKURAN WAKTU KERJA PRODUKSI KASUR PADA USAHA BAPAK PURWANTO DI TANJUNG SELOR - Abriyanto, Arif (EKONOMIA, 2012)
Measurement of working time is one of the tools that companies use to calculate labor productivity in employees. Developing countries in terms of the productivity will always be linked and directed at all the work done with the use of existing human resources. one tool to determine the firm's labor productivity and working time measure of labor standards. By measuring the time standard, companies can plan the amount of labor required, the volume of production, and the wage system in addition to the right company can provide massive incentives to the workforce as an additional incentive or motivation for workers.To determine the standard labor time labor mattress maker type number 2 with a size of 120 x 200 Cm both standard size 12 cm and 15 cm thick on Mr. PURWANTO’s business in Mangga Street Gg. 4 No. 25 Tanjung Selor that manufactures mattresses used standard working time. based on interviews with employers mattress time to complete one (1) piece mattress average - average time required for the completion of a standard size 456 minutes (7.6 hours) and for the thick 852 minutes (14.2 hours).